Analysis of cybersecurity competencies: Recommendations for telecommunications policy - Szczepaniuk, Edyta Karolina; Szczepaniuk, Hubert (Telecommunications policy, 2022)
The paper aims to analyse and assess cybersecurity competencies and define the recommended solutions to improve the human factor in cybersecurity. The article presents the results of theoretical and empirical research that were carried out in 2019–2021. The research subject constitutes one of the priorities of many countries and international organisations. Cybersecurity is one of the essential foundations for implementing the idea of sustainable development. A cybersecurity analysis using a layered structure was proposed in the theoretical part. Empirical research was conducted using a diagnostic poll method based on a survey. The presentation of the research results includes an analysis of statistical dependencies. The paper presents the research results on cybersecurity competencies in the field of threats to state cyberspace and methods of securing and protecting data. An important element of the research was to identify forms of education that can be used to achieve greater efficiency in increasing cybersecurity competencies. The result of the implementation of the research objectives was the development of recommended solutions facilitating the improvement of the human factor in the field of cybersecurity. •The survey results showed diverse cybersecurity competencies, which are an essential element of sustainable development.•The level of knowledge of cyber threats depends on education, age, and training.•The increase in knowledge about cyber threats positively correlates with the intensification of data protection methods used.•We examined the factors influencing the effectiveness of increasing cybersecurity competencies among employees.•Improving cybersecurity competencies can be achieved through education (courses, training, information campaigns).